Electrocoagulation of wastewater from commercial mixing stations with dual aluminum electrode - NI Kuan; SHAN Xiaoli; QI Dong; LI Qiang; ZHANG Wenjun (Gongye shui chuli)
A dual aluminum electrode electrocoagulation method was proposed to achieve efficient flocculation settlement and clarification regeneration of strongly alkaline wastewater from commercial mixing station without agents. The turbidity variation of wastewater from commercial mixing stations with electrolysis time, operating voltage, and electrode configuration mode was investigated through orthogonal experiments, and the effects of three factors on floc chord length were examined using focused beam reflectance measurement(FBRM). The results of the orthogonal experiments showed that the operating voltage had the greatest significance,followed by the electrode configuration mode,whereas the electrolysis time had the least significant impact. The analysis of flocculation chord length showed that the size and strength of the floc increased with the increase of operating voltage and electrolysis time, and the strength of flocs generated in the unipolar parallel mode(MP-P) was the highest. When using MP-P mode, operating voltage of 30 V, and electrolysis time of 15 min, the coagulation and clarification effect of wastewater from commercial mixing station was the best. The turbidity of the wastewater could be reduced to below 69.8 NTU, and the turbidity removal rate could reach over 93%. In addition, the average chord length growth rate of the flocs was the fastest and the strength was the highest. Compared with traditional chemical flocculation, electrocoagulation could avoid secondary pollution of circulating water during the treatment process, and would not have adverse effects on the process performance of concrete, providing a new method for the scientific and efficient purification and reuse of wastewater from commercial mixing stations.